KERAGAMAN MIKOFLORA TANAH PADA HABITAT TANAMAN PISANG DI BALI - l MADE SUDARMA; D.N. SUPRAPTA; Rai Maya Temaja (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2011)
Fungi in the soil plays an important role in maintaining the health and quality ofland, one of several indicators of soil health that is the diversity of soil fungi. This study was done in order to know the soil fungi diversity in the soil of banana plants habitat. The soil samples were collected from three regencies in Bali, i.e. Karangasem, Klungkung and Jembrana which are the main banana growing areas in Bali. Soil sampling was done in two sites in each regency, by collecting 100 grams of soil surrounding the banana plant at the depth of 20 cm, with three replication. Soil microbes population density particularly for bacteria, fungi and actinomycetes were determined based on plate account technique, while the microbes diversity was determined based on Diversity Index of Shannon-Wiener. Diversity index of soil fungi of all soil samples ranged from 0.8785 to 2.1458 (criteria oflow to moderate), with population densities ranging from 1.1 x 104 to 2.8 x 104 cfu / g soil. Evenness index at all sites soil samples obtained ranged from 0.6688 to 0.9766, this means the fungus species found there are no outstanding domination. Similarity index on all soil samples showed less than 0.5, which means one does not have a kinship with each other. Physicochemical factors that affect population density of soil fungi on the banana plant habitats: organic C, total N, available P, available K, soil moisture content (air dry capacity and field capacity), sand and clay. W hile soil physicochemical factors that influence the number of species (diversity) of soil fungi namely: C-organic content, total N and the dust has positive influence on the number of species in banana plants habitat, whereas soil sand content negatively affected the number of types of soil fungi.